PROFIL MAHASISWA DROP OUT PADA JURUSAN SOSIOLOGI FISIP UNIVERSITAS RIAU - Zenni Karlina; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted on the students drop out in Sociology majoring in Social Sciences and Political Science Faculty of Riau University. This research is titled the students profile drop out. This research aims to know the student profile drop out of your Physic Sociology Departement and to know the driving factor of the drop out student at the Departement of Physic Sociology of Riau University. The subject of this study amounted to seven respondents and key informant. The method used in this research is qualitative. The data collection techniques in this study are observations, interviews and documentation. The data source used is primary and secondary data. This research data analysis is a qualitative descriptive. The results of researchers in general can be seen from the existence of several factors that cause students to drop out such as lack of motivation to learn, looking for work, family economic conditions, expensive education costs, and the environment in which they live. Termination of student status or dropping out is the process of revoking student status on a student, due to certain things that have been determined by the university concerned. Student dropping out of the sociology department get four evaluations because GPA and SKS do not meet the requirements. Keywords: Student, Drop Out